AIDS and dualism: Ethiopia's burden under rational expectations - Clive Bell; Anastasios Koukoumelis (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
An AIDS epidemic threatens Ethiopia with a long wave of premature adult mortality, and thus with an enduring setback to capital formation and economic growth. The authors develop a two-sector model with three overlapping generations and intersectorally mobile labor, in which young adults allocate resources under rational expectations. They calibrate the model to the demographic and economic data, and perform simulations for the period ending in 2100 under alternative assumptions about mortality with and without the epidemic. Although the epidemic does not bring about a catastrophic economic collapse, which is hardly possible in view of Ethiopia's poverty and high background adult mortality, it does cause a permanent, downward displacement of the path of output per head, amounting to 10 percent in 2100. An externally funded program to combat the disease is socially very profitable.
Keywords: I10; I20; O11; O41; 330; HIV/AIDS; Growth; Dualism; Ethiopia; AIDS; Bevölkerungsökonomie; Dualökonomie; Rationale Erwartung; Wirtschaftswachstum; Wirtschaftsprognose; Gesundheitspolitik; Wirtschaftspolitische Wirkungsanalyse; Simulation; Äthiopien